Upaya Meningkatkan Hasil Belajar Peserta Didik Melalui Metode Word Square Pada Pembelajaran Tematik Tema Lingkungan Bersih, Sehat, Dan Bersih Di Sekolah Dasar - Yanti Vera (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dharmas Indonesia, 2021)
The problem in this study is the selection of the right learning method for students, the lack of active students in learning at school. The purpose of this study is to improve and improve student learning outcomes through the word square method in thematic learning on the theme of a clean, healthy and clean environment in elementary schools. This research focuses on student learning outcomes. This research is included in classroom action research (CAR) which intends to make changes in learning for students. The subjects of this study were the students of SDN 01 Koto Baru 1.c totaling 24 students. Consisting of 13 males and 11 females. The data collection techniques used are tests and observations. This test is intended to assess the results of scientific studies conducted by students. Observation aims to capture the activities of students in the scientific learning process. The results of this study experienced an increase in both the first and second cycles, in the first cycle the ability of 72.5% increased to 79.16 with a score of 84.83, while in the second cycle to 87.5% with a score of 88.1. In the affective domain, there was an increase of 121 points with a completeness level of 56% (low). Emotional ability scored 154 pints with a classic 71.2% (high). In stage two, the emotional aspect reached 179 classical points 82.8 (high), psychomotor 175 classical points 81% (high).